Optimizing Extraction of Cellulose and Preparing Carboxymethyl Cellulose from Young Longan Fruit Waste - Maneewong, Chutamas; Changkhaochai, Kanyapak; Detchewa, Pakkawat (Journal of Food Technology, Siam University, 2023)
Young longan fruit is an agricultural waste from longan tree pruning. Young longan consists of cellulose, which could be synthesized into carboxymethylcellulose (CMC) for using as a food additive. The aims of this study were to optimize conditions for cellulose extraction from young longan fruit and to characterize the CMC prepared from the extracted cellulose. From the results, young longan fruit powder consisting of 13.5 % cellulose, 13.1 % hemicellulose and 11.7 % lignin (w/w). The conditions for cellulose extraction to produce high yield of crude cellulose (65.61 %) obtained from hydrolysis with the ratio of NaOH (6.0 %): longan powder with (80:20) extracting at 30 oC for 2 h. The crude cellulose was used to synthesize into CMC and confirmed CMC chemical structure by FTIR comparing with commercial CMC. The FTIR absorption band at 3415 cm-1 and 1628 cm-1 corresponded to hydroxy group (-OH) and carboxyl group (COOH) in polysaccharide, respectively. The viscosity of the prepared CMC was 1574 cP and the purity was 81.34 %, there was no statistically significant difference between the prepared CMC and commercial CMC. Thus, young longan waste could be produced to CMC to use in food products.